Predicting the Bond Quality of Heavy Copper Wire Bonds using a Friction Model Approach - Althoff, Simon
Ultraschall-Drahtbonden ist eine Standardtechnologie im Bereich der Aufbau- und Verbindungstechnik von Leistungshalbleitermodulen. Um Prozessschritte und damit wertvolle Zeit zu sparen, sollen die Kupferdickdrähte für die Leistungshalbleiter auch für die Kontaktierung von eingespritzten Anschlusssteckern im Modulrahmen verwendet werden. Das Kontaktierungsverfahren mit diesen Drähten auf Steckern in dünnwandigen Kunststoffrahmen führt häufig zu unzureichender Bondqualität. In dieser Arbeit wird das Bonden von Anschlusssteckern experimentell und anhand von Simulationen untersucht, um die Prozessstabilität zu steigern. Zunächst wurden Experimente auf Untergründen mit hoher Steifigkeit durchgeführt, um Störgrößen von Untergrundeigenschaften zu verringern. Die gewonnenen Erkenntnisse erlaubten die Entwicklung eines Simulationsmodells für die Vorhersage der Bondqualität. Dieses basiert auf einer flächenaufgelösten Reibarbeitsbestimmung im Fügebereich unter Berücksichtigung des Ultraschallerweichungseffektes und der hierdurch entstehenden hohen Drahtverformung. Experimente an den Anschlusssteckern im Modulrahmen zeigten eine verringerte Relativverschiebung zwischen Draht und Stecker, was zu einer deutlichen Verringerung der Reibarbeit führt. Außerdem wurden verminderte Schwingamplituden des Bondwerkzeugs nachgewiesen. Dies führt zu einer weiteren Reduktion der Reibarbeit. Beide Effekte wurden mithilfe eines Mehrmassenschwingers modelliert. Die gewonnenen Erkenntnisse und die erstellten Simulationsmodelle ermöglichen die Entwicklung von Klemmvorrichtungen, welche die identifizierten Störgrößen gezielt kompensieren und so ein verlässliches Bonden der Anschlussstecker im gleichen Prozessschritt ermöglichen, in dem auch die Leistungshalbleiter kontaktiert werden.
Keywords: heavy copper bonding; wire bonding; quality prediction; friction model; point-contact-element

Analysis of temperature effect on strength and microstructure in friction induced recycling process (FIRP) - Borgert, Thomas; Homberg, Werner (Materials Research Proceedings)
Abstract. In order to reduce global energy consumption in production and industry along with the associated CO2 emissions, existing resources must be used more efficiently. This includes the energy-efficient and comprehensive recycling of a wide range of metals. Especially for the production of aluminium, there is a large potential for saving energy using efficient recycling processes. With regard to the recycling of aluminium studies have shown that solid-state recycling processes are significantly more efficient considering the used energy and resources compared to the conventional, smelting-metallurgical recycling process. In this paper, the direct and energy-efficient friction-induced recycling process (FIRP) based on the conform process is further described and analysed in terms of the temperature-property relationships. For this purpose, the influence of the processing temperature on the microstructure and properties of the recycled semi-finished products is investigated using the toll system that enables an ECAP forming. Specific sections of the (in theory) infinite, recycled semi-finished product are taken and analysed at different process temperatures of the solid state recycling process. Based on these sections, the properties in terms of mechanical hardness, strength, ductility and grain size are analysed and a degressive relationship between process temperature and mechanical hardness up to a temperature of 270 °C can be shown. Applying the Hall-Petch relationship, it is analysed whether there is a correlation between the strength and the microstructure in the form of the grain size.
Keywords: Recycling; Aluminium; Friction-Induced; Energy Efficiency

Influence of the Rivet Coating on the Friction during Self-Piercing Riveting - Uhe, Benedikt; Kuball, Clara-Maria; Merklein, Marion; Meschut, Gerson (Key Engineering Materials)
The number of multi-material joints is increasing as a result of lightweight design. Self-piercing riveting (SPR) is an important mechanical joining technique for multi-material structures. Rivets for SPR are coated to prevent corrosion, but this coating also influences the friction that prevails during the joining process. The aim of the present investigation is to evaluate this influence. The investigation focuses on the common rivet coatings Almac® and zinc-nickel with topcoat as well as on uncoated rivet surfaces. First of all, the coating thickness and the uniformity of the coating distribution are analysed. Friction tests facilitate the classification of the surface properties. The influence of the friction on the characteristic joint parameters and the force-stroke curves is analysed by means of experimental joining tests. More in-depth knowledge of the effects that occur is achieved through the use of numerical simulation. Overall, it is shown that the surface condition of the rivet has an impact on the friction during the joining process and on the resulting joint. However, the detected deviations between different surface conditions do not restrict the operational capability of SPR and the properties of uncoated rivet surfaces, in particular, are similar to those of Almac®-coated rivets. It can thus be assumed that SPR with respect to the joining process is also possible without rivet coating in principle.
Keywords: Coating; Friction; Joining

Co-simulation of MATLAB and ANSYS for ultrasonic wire bonding process optimization - Schemmel, Reinhard; Krieger, Viktor; Hemsel, Tobias; Sextro, Walter (Microelectronics Reliability)
Ultrasonic wire bonding is a solid-state joining process, used in the electronics industry to form electrical connections, e.g. to connect electrical terminals within semiconductor modules. Many process parameters affect the bond strength, such like the bond normal force, ultrasonic power, wire material and bonding frequency. Today, process design, development, and optimization is most likely based on the knowledge of process engineers and is mainly performed by experimental testing. In this contribution, a newly developed simulation tool is presented, to reduce time and costs and efficiently determine optimized process parameter. Based on a co-simulation of MATLAB and ANSYS, the different physical phenomena of the wire bonding process are considered using finite element simulation for the complex plastic deformation of the wire and reduced order models for the transient dynamics of the transducer, wire, substrate and bond formation. The model parameters such as the coefficients of friction between bond tool and wire and between wire and substrate were determined for aluminium and copper wire in experiments with a test rig specially developed for the requirements of heavy wire bonding. To reduce simulation time, for the finite element simulation a restart analysis and high performance computing is utilized. Detailed analysis of the bond formation showed, that the normal pressure distribution in the contact between wire and substrate has high impact on bond formation and distribution of welded areas in the contact area.
Keywords: Ultrasonic heavy wire bonding; Co-simulation; ANSYS; MATLAB; Process optimization; Friction coefficient; Copper-copper; Aluminium-copper

Using complex multi-dimensional vibration trajectories in ultrasonic bonding and welding - Schemmel, Reinhard; Hemsel, Tobias; Dymel, Collin; Hunstig, Matthias; Brökelmann, Michael; Sextro, Walter (Sensors and Actuators A: Physical)
Ultrasonic joining is a common industrial process. In the electronics industry it is used to form electrical connections, including those of dissimilar materials. Multiple influencing factors in ultrasonic joining are known and extensively investigated; process parameters like ultrasonic power, bond force, and bonding frequency of the ultrasonic vibration are known to have a high impact on a reliable joining process and need to be adapted for each new application with different geometry or materials. This contribution is focused on increasing ultrasonic power transmitted to the interface and keeping mechanical stresses during ultrasonic bonding low by using a multi-dimensional ultrasonic transducer concept. Bonding results for a new designed connector pin in IGBT-modules achieved by multi- and one-dimensional bonding are discussed.
Keywords: Ultrasonic bonding; Ultrasonic welding; Multi-dimensional bonding; Complex vibration; Multi-frequent; Two-dimensional friction model

A Mechanical Model for the Dynamical Contact of Elastic Rough Bodies with Viscoelastic Properties - Schulte, Frank; Neuhaus, Jan; Sextro, Walter (Proceedings of ICoEV 2015 International Conference on Engineering Vibration)
The contact between viscoelastic materials e.g. elastomers and a rough surface leads to a special friction characteristic, which differs greatly in its properties comparing to other materials like metals. In practice, this friction combination occurs for example in the tire-road contact, or in the use of rubber gaskets. Due to the frictional forces a system is significantly influenced in its vibrational properties. The friction force is composed of two main components adhesion and hysteresis. The adhesion results from molecular bounds between the contact partners, while the deformation of the viscoelastic material by the roughness of the counter body leads to power loss. This internal friction results in an additional frictional force, which is described by the hysteresis. To simulate the frictional behaviour of elastomers on rough surfaces and thus to determine the energy dissipation in contact, it is necessary to develop a mechanical model which considers the roughness of the contact partners, as well as dynamic effects and the dependence on normal pressure and sliding speed. The viscoelastic material behaviour must also be considered. The contact between two rough surfaces is modelled as a rough rigid layer contacting a rough elas- tic layer. The elastic layer is modelled by point masses connected by Maxwell-elements. This allows the viscoelastic properties of the elastomer to be considered. The behaviour of whole system can be described by equations of motion with integrated constraints. The degrees of freedom of the model depends on the varying contact conditions. A point mass not in contact has two degrees of freedom. A point mass in contact moving along the roughness path can be described by only one degree of freedom. For each Maxwell-Element also an inner coordinate and thus a further degree of freedom is needed. Because of varying contact conditions dur- ing the simulation, the simulation interrupts in case the contact conditions change. Then the equations of motions are adapted with respect to the contact constraints. As a result of the simulation one obtain the energy dissipation and thus the friction char- acteristic during the friction process. It is possible to use these results in three dimensional point-contact elements in order to model contact surfaces on lager length scales.
Keywords: Contact Mechanics; Viscoelastic Material; Adhesive Friction; Hysteresis Friction; Energy Dissipation; Vibration

Improving the bond quality of copper wire bonds using a friction model approach - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (Electronic Components and Technology Conference (ECTC), 2014 IEEE 64th)
In order to increase mechanical strength, heat dissipation and ampacity and to decrease failure through fatigue fracture, wedge copper wire bonding is being introduced as a standard interconnection method for mass production. To achieve the same process stability when using copper wire instead of aluminum wire a profound understanding of the bonding process is needed. Due to the higher hardness of copper compared to aluminum wire it is more difficult to approach the surfaces of wire and substrate to a level where van der Waals forces are able to arise between atoms. Also, enough friction energy referred to the total contact area has to be generated to activate the surfaces. Therefore, a friction model is used to simulate the joining process. This model calculates the resulting energy of partial areas in the contact surface and provides information about the adhesion process of each area. The focus here is on the arising of micro joints in the contact area depending on the location in the contact and time. To validate the model, different touchdown forces are used to vary the initial contact areas of wire and substrate. Additionally, a piezoelectric tri-axial force sensor is built up to identify the known phases of pre-deforming, cleaning, adhering and diffusing for the real bonding process to map with the model. Test substrates as DBC and copper plate are used to show the different formations of a wedge bond connection due to hardness and reaction propensity. The experiments were done by using 500 $μ$m copper wire and a standard V-groove tool.
Keywords: adhesion; circuit reliability; deformation; diffusion; fatigue cracks; friction; interconnections; lead bonding; van der Waals forces; Cu; adhering process; adhesion process; ampacity improvement; bond quality improvement; cleaning process; diffusing process; fatigue fracture failure; friction energy; friction model; heat dissipation; mechanical strength; piezoelectric triaxial force sensor; predeforming process; size 500 mum; total contact area; van der Waals forces; wedge copper wire bonding; Bonding; Copper; Finite element analysis; Force; Friction; Substrates; Wires

High-velocity operation of piezoelectric inertia motors: experimental validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Archive of Applied Mechanics)
Piezoelectric inertia motors use the inertia of a body to drive it by means of a friction contact in a series of small steps. It has been shown previously in theoretical investigations that higher velocities and smoother movements can be obtained if these steps do not contain phases of stiction (''stick-slip`` operation), but use sliding friction only (''slip-slip`` operation). One very promising driving option for such motors is the superposition of multiple sinusoidal signals or harmonics. In this contribution, the theoretical results are validated experimentally. In this context, a quick and reliable identification process for parameters describing the friction contact is proposed. Additionally, the force generation potential of inertia motors is investigated theoretically and experimentally. The experimental results confirm the theoretical result that for a given maximum frequency, a signal with a high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion, while the maximum motor force is obtained with signals containing more harmonics. These results are of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Inertia motor; High velocity; Stick-slip motor; Slip-slip operation; Friction parameter identification

A comprehensive model of wear, friction and contact temperature in radial shaft seals - Frölich, D.; Magyar, Balázs; Sauer, B. (Wear)
Radial shaft seals are used in a variety of applications, where rotating shafts in steady housings have to be sealed. Typical examples are crankshafts, camshafts, differential gear or hydraulic pumps. In the operating state the elastomeric seal ring and the shaft are separated by a lubrication film of just a few micrometers. Due to shear strain and fluid friction the contact area is subject to a higher temperature than the rest of the seal ring. The stiffness of the elastomeric material is intensely influenced by this temperature and thus contact pressure, friction and wear also strongly depend on the contact temperature. In order to simulate the contact behavior of elastomer seal rings it is essential to use a comprehensive approach which takes into consideration the interaction of temperature, friction and wear. Based on this idea a macroscopic simulation model has been developed at the MEGT. It combines a finite element approach for the simulation of contact pressure at different wear states, a semi-analytical approach for the calculation of contact temperature and an empirical approach for the calculation of friction. In this paper the model setup is presented, as well as simulation and experimental results.
Keywords: Radial shaft seal ring; Contact temperature; Wear; Friction torque; Finite element simulation

A friction based approach for modeling wire bonding - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (IMAPS 2013, 46th International Symposium on Microelectronics)
A model approach for wedge/wedge bonding copper wire is presented. The connection between wire and substrate is based on a variety of physical effects, but the dominant one is the friction based welding while applying ultrasound. Consequently, a friction model was used to investigate the welding process. This model is built up universal and can be used to describe the formation of micro welds in the time variant contact area between wire and substrate. Aim of the model is to identify the interactions between touchdown, bond normal force, ultrasonic power and bonding time. To do so, the contact area is discretized into partial areas where a Point Contact Model is applied. Based on this approach it is possible to simulate micro and macro slip inside the contact area between wire and substrate. The work done by friction force is a main criterion to define occurring micro joints which influence the subsequent welding.
Keywords: Wire bonding; friction modeling; wire bond quality; contact element modeling